RANCANG BANGUN PEMBANGKIT LISTRIK TENAGA MIKROHIDRO DENGAN PEMANFAATAN ALIRAN ANAK SUNGAI MENGGUNAKAN CONTINUOSLY VARIABLE TRANSMISSION - Lanang Legawa, I Nyoman; Indra Partha, Cokorde Gede; Janardana, I Gusti Ngurah (Jurnal SPEKTRUM; Vol 11 No 4 (2024): Jurnal SPEKTRUMDO - 10.24843/SPEKTRUM.2024.v11.i04.p9, 2024)
ndonesia has set ambitious targets to increase the share of renewable energy in its energy mix, with Micro-Hydro Power Plants (PLTMH) being one of the renewable energy solutions. This study focuses on developing a PLTMH utilizing the flow of the Tukad Sungi tributary in Banjar Ganter, Desa Abian Tuwung, employing a Continuously Variable Transmission (CVT) as the transmission mechanism between the turbine and generator. A water flow rate of 0.44 m³/s was capable of generating up to 8.580 kW, while a flow rate of 0.026 m³/s was used to produce a hydraulic power of 484.12 watts and a generator output of 313.227 watts. Testing revealed a decrease in turbine speed from 527.88 rpm to 315.8 rpm (40%), while the generator speed increased from 315.8 rpm to 1509.8 rpm (378%). Although the CVT improved generator speed, the system efficiency decreased due to the inability of the CVT to stabilize rotations and the occurrence of v-belt slippage caused by water splashes. The reduction in turbine speed and insufficient torque indicated that the CVT's performance was not significantly different from that of conventional pulley systems.